Translation Procedure of English to Indonesian Subtitle 'English Vinglish' Movie - Fitria, Tira Nur (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2020)
The objectives of this research are to find the types and the most dominant type of translation procedures of English into Indonesian Subtitle in Ã¢â‚¬Å“English VinglishÃ¢â‚¬Â Movie. This research is descriptive qualitative research. The data of this study are the words, clauses, and sentences in the subtitle movie both English and Indonesian. Data source is taken from Ã¢â‚¬Å“English VinglishÃ¢â‚¬Â Movie. The data collection procedure in this research is document analysis. From the result, it shows that the translation procedures used in subtitle English Vinglish movie consist of direct translation and oblique translation. In direct translation, it consists of literal translation as 148 data or 34.89%, borrowing as 82 data or 20.39 %, and calque as 0 data or 0 %. While, in oblique translation consist of transposition as 76 data or 18.67 %, equivalence as 62 data or 15.23 %, modulation as 32 data or 7.86 %, and adaptation as 6 data or 1.47 %. The most dominant type of translation procedures of English into Indonesian Subtitle in Ã¢â‚¬Å“English VinglishÃ¢â‚¬Â Movie is in direct translation, especially in literal translation. Keywords: Subtitle, Translation, Translation Procedure